Keberkesanan program pembangunan ekonomi asnaf oleh Lembaga Zakat Selangor / Khairul Azhar Meerangani and Ummi Khasidah Zaham Azman - Meerangani, Khairul Azhar; Zaham Azman, Ummi Khasidah (2019)
The Asnaf Economic Programme is one of initiatives that has been planned and implemented by Lembaga Zakat Selangor (LZS) with the purpose of helping asnafs to groom their potentials in the entrepreneurship sector. The objective of the programme is in line with the zakat's own goals in ensuring that each asnaf is able to become independent and to build his or her own potentials in alleviating poverty. Various assistance in the form of capital injection and provision of equipment have been provided to the asnaf in achieving objectives of the programme. The study was conducted to identify factors influencing involvement and participation of the asnafs in the programme as well as to assess the programme effectiveness in improving life status and quality of each asnaf who involves in the programme. This study focuses on asnaf entrepreneurs in Kuala Selangor Distric and an interview method was used to get responses from each participant regarding the programme. A total of 8 aspiring entrepreneurs who participated in the programme were interviewed to gain their views on the effectiveness of the programme. In addition, the researcher used library data to obtain information related to the Asnaf Economic Programme itself. The results show that LZS has successfully produced a group of asnaf entrepreneurs through its economic programme. It has also provided a better life to the participants and reduced the number of asnafs in Selangor, specifically in Kuala Selangor area. In other words, the programme helps to increase the number of zakat payers to benefit unprivileged groups as well as to become role models to the other asnafs in that particular area. However, a thorough assessment of the programme has to be done by LZS in order to improve the quality and effectiveness of the programme in the future.